3/6 x 2/2 = 6/12
1/4 x 3/3 = 3/12
6/12 - 3/12 = 3/12 = 1/4
Answer: 1 quarter
-------------------------------------
3/6 - 1/4 = (1×3)/(2×3) - 1/4
= 1/2 - 1/4
= (1×2)/(2×2) - 1/4
= 2/4 - 1/4
= 1/4
Two minus 4/6 is 1 1/3.
It is: 1/6 minus 2/3 = -1/2
1
2/3 can be converted to 4/6. So 4/6 - 1/6= 3/6 or 1/2
1 1/3 minus 2/6 is 1.
Two minus 4/6 is 1 1/3.
It is: 1/6 minus 2/3 = -1/2
1
It is: -1/3
1- 18th
2/3 can be converted to 4/6. So 4/6 - 1/6= 3/6 or 1/2
3 and 1/6
It is: 2 and 1/2 minus 1/6 = 7/3 or as 2 and 1/3
1 1/3 minus 2/6 is 1.
1/2
The answer is 0. 2/6-1/3=0
2/3 minus 1/6 is the same as 4/6 minus 1/6 = 3/6 or 1/2 simplified